Co‐occurrence of 22q11 deletion syndrome and hdr syndrome. Issue 10 (5th August 2013) - Fukai, Ryoko; Ochi, Nobuhiko; Murakami, Akira; Nakashima, Mitsuko; Tsurusaki, Yoshinori; Saitsu, Hirotomo; Matsumoto, Naomichi; Miyake, Noriko
ABSTRACT 22q11 deletion syndrome is one of the most common chromosomal deletion syndromes and is usually caused by a 1.5–3.0 Mb deletion at chromosome 22q11.2. It is characterized by hypocalcemia resulting from hypoplasia of the parathyroid glands, hypoplasia of the thymus, and defects of the cardiac outflow tract. We encountered a Japanese boy presenting with an unusually severe phenotype of 22q11 deletion syndrome, including progressive renal failure and severe intellectual disabilities. Diagnostic testing using fluorescent in situ hybridization revealed deletion of the 22q11 region, but this did not explain the additional complications. Copy number analysis was therefore performed using whole genome single nucleotide polymorphism (SNP) assay, which identified an additional de novo deletion at 10p14. This region is the locus for hypoparathyroidism, deafness, and renal dysplasia (HDR) syndrome caused by haploinsufficiency of GATA3. Together, these two syndromes sufficiently explain the patient's phenotype. This is the first known case report of the co‐occurrence of 22q11 deletion syndrome and HDR syndrome. As the two syndromes overlap clinically, this study indicates the importance of carrying out careful clinical and genetic assessment of patients with atypical clinical phenotypes or unique complications. Unbiased genetic analysis using whole genome copy number SNP arrays is especially useful for detecting such rare double mutations. © 2013 Wiley Periodicals, Inc.